ADMINISTRATIVE CONTRACTS IN THE LIGHT OF NEW FORMS OF MANAGEMENT AND SUSTAINABILITY: FOR THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT IN BRAZIL - Diz, Jamile Bergamaschine Mata (PANORAMA OF BRAZILIAN LAW, 2019)
The legal inclusion of environmental considerations in public contracts becomes a reality to be observed by public authorities in order to achieve the constitutionally established principle of sustainable development. To effectively be able to assess the incorporation of environmental concerns at all stages of forming the administrative contract, emphasizing the sustainability of it, it is necessary to adopt planning mechanisms, implementation, evaluation and monitoring, if the so-called PDCA cycle (acronym for Plan, Do, Check and Action). Thus, this study aims to analyze the issue of sustainable procurement, focusing on the stages of the administrative agreement by the PDCA method, seeking to establish to what extent we can assess and measure the sustainability practice by the Public Administration for subsequently case study of administrative contracts signed by the São Paulo Court of Justice.